Analysis of the Relationship Between Internal and External Gaps and GDP in Iraq for the Period (2004-2022) - Majeed Mazhar, Huda; Jawad, Sajja (Journal of Economics and Administrative Sciences, 2025)
This paper deals with studying the relationship between internal and external gaps and the gross domestic product in Iraq for the period (2004-2022), as the Iraqi economy suffers from a financing problem, and this problem has resulted in a weak link between the economic sectors, high inflation rates, as well as the inability of the economic policies followed to achieve the required financing, so the research problem can be clarified by asking about the impact of internal and external gaps on the gross domestic product.  Inductive and quantitative approaches were adopted, which relied on the joint integration methodology to show the impact of internal and external gaps on the gross domestic product in Iraq for the period (2004-2022), and the (EViews13) program was used. According to the Phillips-Perron unit root test results, all variables are stationary at the level of the first difference but non-stationary at the second difference. This makes it possible to use the ARDL model. The existence of joint integration, or a long-term equilibrium relationship between the research variables, was validated by the ARDL model bounds test results. Practical implications include policy recommendations to reduce deficits and stabilize growth. Socially, it addresses economic disparities, promoting equitable wealth distribution and sustainable development by identifying key drivers of economic performance. This study provides a unique perspective by analyzing the dual influence of internal and external economic gaps on Iraq's GDP, offering data-driven insights for policymakers to foster sustainable economic growth.